واقع المعالجة البيداغوجية و التقويم التربوي في التعليم الابتدائي - عوار اسماء (كلية العلوم الاجتماعية, 2020)
ملخص الدراسة : تهدف هذه الدراسة إلى محاولة فهم واقع المعالجة البيداغوجية ومدي فاعلية التقويم التربوي في مواجهة المشكلات الدراسية و التأخرات التعليمية لدى تلاميذ المرحلة الابتدائية , وقد كان تمحور مشكل الدراسة في السؤال التالي : - ما هو واقع المعالجة البيداغوجية في المدارس الابتدائية؟ وهل يعتبر التقويم التربوي ذا فاعلية في تشخيص الصعوبات لدى المتعلمين, ومعالجتها أوليا ؟ وللإجابة عن هذا التساؤل اقترحت الفرضيات التالية : - يقوم التقويم التربوي على طريقتين الأولى : تقليدية والثانية :حديثة. - يعتمد المعلمون على الاختيار العشوائي لذوي الصعوبات. - يتم تشخيص الصعوبات عن طريق بطاقات المعالجة وفق معايير محددة, وأخيرا: التقويم التربوي يعتمد على امتحانات كتابية وشفهية . تم الاعتماد على المنهج الوصفي قصد جمع البيانات ووصفها باعتباره من المناهج الأكثر استعمال في العلوم الاجتماعية والإنسانية, ويعبر عن الظاهرة التي هي محل الدراسة,وتمثلت العينة في تلاميذ ذو صعوبات تعليمية مختلفة وأساتذة لمختلف المراحل التعليمية وبعض المختصين في مجال التربية والتعليم من مفتشين ومدراء مهتمين بالتقويم التربوي والمعالجة البيداغوجية. توصلت نتائج الدراسة إلى أن: - المعالجة البيداغوجية موجودة إلا أن فاعليتها مرتبطة بمنهجية تطبيقها وأنها ساهمت في تخطي العديد من التعثرات الدراسية , مرافقة للتقويم التربوي المؤهل و الدقيق لكل صعوبة تعليمية لدي التلاميذ بأخذ الاعتبار لفروقهم الفردية وتنوع قدراتهم الفكرية. Study summary: This study aims to try to understand the reality of pedagogical treatment and the effectiveness of the educational evaluation in the face of academic problems and educational delays among primary school students. The study problem was centered on the following question: What is the reality of pedagogical treatment in primary schools? Is the educational evaluation effective in diagnosing the difficulties of the learners and treating them first? To answer this question, the following hypotheses were proposed: The educational evaluation is based on two methods: the first is traditional and the second is modern. Teachers rely on random selection for people with difficulties. - Difficulties are diagnosed by treatment cards according to specific criteria, and finally: The educational evaluation depends on written and oral exams. The descriptive approach was relied upon in order to collect data and describe it as one of the most used curricula in social and human sciences, and it expresses the phenomenon that is being studied. Educational and pedagogical treatment. The results of the study found that: - Pedagogical treatment exists, but its effectiveness is related to the methodology of its application, and it has contributed to overcoming many academic obstacles, accompanying the qualified and accurate educational evaluation of each educational difficulty of students by taking into account their individual differences and the diversity of their intellectual capabilities.
Keywords: التقويم التربوي؛المعالجة البيداغوجية؛